2007
DOI: 10.1007/s00417-007-0670-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased retinal toxicity of intravitreal tissue plasminogen activator in a central retinal vein occlusion model

Abstract: Retinal toxicity associated with intravitreally injected tPA can increase in a dose-dependent manner and be exacerbated in CRVO eyes, suggesting that the dose of tPA should be reduced when tPA is used to treat eyes with CRVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…There has been concern that tPA can lead to retinal toxicity. [31][32][33] In our study, we saw nothing to indicate any patients developed retinal toxicity in either treatment group.…”
Section: Discussionmentioning
confidence: 61%
“…There has been concern that tPA can lead to retinal toxicity. [31][32][33] In our study, we saw nothing to indicate any patients developed retinal toxicity in either treatment group.…”
Section: Discussionmentioning
confidence: 61%
“…The CRVO model was established as previously described. 12,13 Briefly, immediately after an injection of rose bengal (2 mg/kg; Nacalai Tesque, Kyoto, Japan) into the tail vein, a laser was applied to the major retinal veins adjacent to the optic nerve head to induce a thrombus. The laser settings were as follows: wavelength, 514 nm; spot size, 50 m; power, 100 mW; duration, 0.5 second; and number of applications, one to three shots for each vein.…”
Section: In Vivo Crvo Modelmentioning
confidence: 99%
“…Accordingly, intravitreal tPA injection may be a promising alternative for patients and physicians who wish to reduce the burden of RVO treatment. It has been reported that tPA showed dose-dependent retinal toxicity [10,11]; tPA-associated retinal toxicity can be exacerbated in CRVO models [12]. Previous studies have assessed the retinal toxicity of intravitreal tPA using full-field electroretinogram (ERG) in human eyes [8,13,14].…”
Section: Introductionmentioning
confidence: 99%